Journal of Prisoners on Prisons, V31 #1 - Piché, Justin (Université d'Ottawa | University of Ottawa, 2022)
This general issue of the Journal of Prisoners on Prisons edited by Justin Piché and Kevin Walby features articles by current and former prisoners documenting the latest trends in penal policy and practice in the United States. The issue also features an article to “The Dialogue on the Canadian Carceral State” that explores the punitiveness of Canada’s immigration system, a “Response” paper on the struggle over the future of the decommissioned Prison for Women (P4W) as a site of memory, as well as “Prisoners’ Struggles” contributions, and a book review. The cover art, featuring the pieces “Carceral Landscape” and “Close the Bastard Down!”, was created by Peter Collins – a former Canadian prisoner serving a life sentence who died behind bars of cancer.
INTRODUCTION FROM THE ISSUE EDITORS Desistance, Social Justice and Lived Experience Katharina Maier, Rosemary Ricciardelli and Shadd Maruna . ARTICLES Desistance, Anomalies and Rabbit Holes: A Transformative Experience from Inside Out Christopher Havens and Marta Cerruti Desistance and Prisoner Re-entry: A Real-time Perspective Kris MacPherson Co-producing Desistance Opportunities with Women in Prison: Refl ections of a Sports Coach Developer Christopher Kay, Carolynne Mason and Tom Hartley Desistance and Prison Culture: A Trifurcated Prisoner Classifi cation Theory Ruth Utnage Twenty Years of Incarceration in the Garden State: Refl ecting on the Barriers and Facilitators in the Desistance Process Stephon Whitley with a forward by Nathan W. Link Captor Story and Captive Story Francis X. Kroncke What Can the Legal Profession Do For Us? Formerly Incarcerated Attorneys and the Practice of Law as a Strengths-Based Endeavour James Binnall The Contradictions of Prisoner Life and Rehabilitation: An Auto-ethnographic Life Sentence Experience Daniel Micklethwaite RESPONSE On Desistance and Resistance Justin Piché PRISONERS’ STRUGGLES A Call for Memorials, Writing and Artwork by Imprisoned People and their Loved Ones Mourning Our Losses COVID-19 Pandemic Struggles of Prisoners’ Families Joanne Fry BOOK REVIEWS Available Titles and Call for Book Reviews Journal of Prisoners on Prisons UPCOMING SPECIAL ISSUES – CALLS FOR PAPERS Homelessness and Incarceration Erin Dej and Dale Spencer Emotions and Carceral Spaces Jennifer Kilty, Rachel Fayter and Justin Piché COVER ART “Transition” (front cover) Steel Door Studios 2022 “Turbulent Tenacity” (back cover) Steel Door Studios 2022
Keywords: Jail; Prisons; penitentiary; incarceration; prison writing; prisoner ethnography; punishment